International Double Degree Programs as Accelerators for Internationalization: Lessons from the Trans-Atlantic Business School Alliance. Issue 1 (2nd January 2021) - Steagall, Jeffrey W.; Falk, Peter; Gallo, Andres; Porter, Thomas W.
ABSTRACT: The global nature of the modern business world has expanded the set of skills and attitudes necessary for success, even among new bachelor degree graduates. Although US business schools have primarily integrated international concepts through their curricula, students who stay at their home institutions for their entire degree programs do not live and experience the global business environment to the extent necessary for twenty-first-century careers. Short-term, semester- or year-abroad programs help to bridge this gap. However, carefully constructed undergraduate double degree programs can provide students with much richer experiences. This article provides a model for creating international undergraduate double degree programs in business, highlighting the main challenges and offering successful proven solutions employed by a group of American and European business schools that other institutions can adapt to accelerate internationalization and deepen students' international experiences in American business schools.